(untitled) (Albayan Scientific Journal, 2023)
This study summarizes the relationship between the leading style and the development of intellectual capital of the study sample, in an effort to understand the nature of this relationship between them, as one of the most important variables contributing to performance. (The intellectual capital) is capital of the basic resources of modern organizations under the knowledge economy, where the development of intellectual capital and investment will not find it to the light unless it is adopted by the administrative leadership in the organization. The organization may not be ignored and the emergence of the development of the development of the integrated capital, which has been a result of the development of the development of the intellectual capital, the organization has been aimed at the development of its human and material manner, which is working to develop the mankind of the workers and the completion of the workforce. The course of the organization is in the context. The following is the work of the relationship The development of the leader of the leader and the development of the relationship between the leading style and the development of the development of the development of the development of the prevailing and the most specificity The study problem is lying in the question: Is the relationship between the leading style and the development of intellectual capital of the capital.